Estimation of Revenue-Based Fishing Capacity of Trawlers Using Data Envelopment Analysis - Pe., Jeyya Jeyanthi; V. Geethalakshmi; V.K. Sajesh; V. Chandrasekar; A.K. Mohanty; Nikita Gopal (Fishery Technology, 2023)
Excess fishing capacity is a major problem of marine capture fisheries both at national and global level which needs urgent attention in the view of resource sustainability. Data Envelopment Analysis (DEA) was applied to estimate the revenue-based fishing capacity using the input and output data of the trawl fishing operations in Ernakulam district, Kerala, India. The analysis used trip-based panel data collected from 10 trawlers comprising of 370 data sets for one year period. The quantitative and economic input and output indicators were collected using the customized logbook. It was found that the trawl fishery operates at 85 % and 74 % of their capacity utilization and technical efficiency levels respectively. The economic utilization of capacity was estimated at 74 percent. The study revealed that the vessels with high technical efficiency also resulted in low economic efficiency indicating ample scope for improving the revenuebased capacity levels. The factors determining the fishing capacity were assessed using Multiple Linear Regression Analysis (MLRA). The results revealed that fishing capacity of trawl fishery is significantly determined by engine power. Deriving the effective fishing capacity is possible when economic parameters are taken into consideration while formulating the policy decisions of fisheries management.